2022
DOI: 10.1016/j.trsl.2022.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes as prognostic biomarkers in pancreatic ductal adenocarcinoma—a systematic review and meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Nevertheless, many meta-analyses have confirmed the unique diagnostic and prognostic value of CTCs [92][93][94][95]. The same properties are attributed by meta-analyses to circulating EVs [96][97][98][99]. We conjecture that both of these laboratory markers will soon be introduced into run-of-the-mill clinical diagnostics and that the interpretation of the results may be helped by artificial intelligence and machine learning [30].…”
Section: Advantages Limitations Pros and Consmentioning
confidence: 73%
“…Nevertheless, many meta-analyses have confirmed the unique diagnostic and prognostic value of CTCs [92][93][94][95]. The same properties are attributed by meta-analyses to circulating EVs [96][97][98][99]. We conjecture that both of these laboratory markers will soon be introduced into run-of-the-mill clinical diagnostics and that the interpretation of the results may be helped by artificial intelligence and machine learning [30].…”
Section: Advantages Limitations Pros and Consmentioning
confidence: 73%
“…Therefore, at present, EVs can only serve as a valid reference in disease diagnosis, and further large-scale studies are required to establish them as a diagnostic standard. A meta-analysis incorporating the detection of positive EV biomarkers of exoDNA KRASmut, ExmiR 451 a, ExmiR 200 b, ExmiR 222, and so on in 634 patients indicated that the presence of positive EV biomarkers in the blood varied in correlation with mortality at different stages of pancreatic ductal adenocarcinoma treatment [ 173 ]. This illustrates the effectiveness of EVs in disease prognosis, as endothelium-derived EVs expressing CD146 and CD105 were significantly predictive of overall survival in metastatic colorectal cancer [ 174 ].…”
Section: Loaded Cargos Of Microneedlesmentioning
confidence: 99%
“…The recent meta-analytic data in the study by Bunduc et al, which included 634 patients from eleven studies, demonstrated several exosomal biomarkers that were correlated with an elevated mortality risk, with their pre-operative levels being increased in resectable cases, compared to non-resectable ones [ 204 ].…”
Section: Evs As Prognostic Tools In Pdacmentioning
confidence: 99%